IMPLEMENTASI PEMBIASAAN POSITIF BERBASIS PENDIDIKAN KARAKTER UNTUK MENGUATKAN PROFIL PELAJAR PANCASILA SISWA SD - Saimin, Saimin; Maria Zulfiati, Heri; Sutrisno, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article aims to illustrate the importance of implementing positive habits in elementary school students to strengthen the profile of Pancasila students. The research method used is a qualitative method with data collection techniques of observation, interviews and documentation. The results of this research show that there are several habituation activities that are carried out routinely in implementing these positive habits, such as instilling positive habits by greeting students, I see the trash must be picked up, lining up before entering, literacy five twelve minutes. The consistent application of positive habits by schools has a positive impact on improving the quality of children's character. In the learning process in elementary school, both in the classroom and outside the classroom, children need to be accustomed to warm situations full of familiarity, respect and empathy. A positive environment will determine the direction of a child's personality in searching for their identity.